Improvements in Antimicrobial Prescribing and Outcomes in Pediatric Complicated Appendicitis. Issue 5 (May 2018) - Willis, Zachary I.; Duggan, Eileen M.; Gillon, Jessica; Blakely, Martin L.; Di Pentima, M. Cecilia
Abstract : Background: Complicated appendicitis, characterized by perforation and/or peritonitis, is common in children, and late infectious complications are frequent. The best antibiotic treatment approach is unknown, resulting in substantial variation in care. We evaluated the effects of 2 successive interventions, an antimicrobial stewardship program (ASP) and a condition-specific clinical practice guideline (CPG), on antimicrobial utilization and patient outcomes in these patients. Methods: The ASP at our institution was begun in March 2012. The CPG, a standardized antibiotic treatment, was implemented in July 2013. We reviewed every case of complicated appendicitis managed with early appendectomy between January 2011 and October 2014. Patients were thus divided into 3 eras based on their exposure to the following: (1) neither intervention, (2) ASP only or (3) both ASP and CPG. We compared measures of antibiotic utilization and clinical outcomes among the 3 eras. Results: A total of 313 patients were included in the study: 91 exposed to neither intervention; 100 exposed to only the ASP; and 122 exposed to both interventions. With ASP implementation, there were declines in the use of unnecessarily broad or toxic antibiotic regimens. With CPG implementation, there was a decrease in total antibiotic utilization and discharges with intravenous antibiotics. Compliance with CPG-recommended antibiotics exceeded 90%. There was no significant change in overall adverse events; there was a decline in the incidence of surgical-site infections in patients exposed to both interventions. Conclusions: Complicated appendicitis is an important target for antimicrobial stewardship and quality improvement efforts. A condition-specific CPG can improve both antimicrobial utilization and clinical outcomes.